EFEKTIVITAS KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUKABUMI - Gemiarty Puteri Yuanita Betha Anugerah (STISIP Widyapuri Mandiri Sukabumi, 2023)
The approach method of this study is a qualitative approach with a descriptiveimethod. Collecting data through iobservation, xinterviews, and documentation. Validation of information data that has been collected by testing credibility through triangulation (technique, source and time) and analysis with reduction techniques, data presentation and drawing conclusions. The informants in this study amounted to 6 people, namely: 1 Village Head of Pasir Datar Indah, 1 Secretary of Pasir Datar Indah Village, 1 Head of Planning for Pasir Datar Indah Village, 1 Head of Welfare Head of Pasir Datar Indah Village, 2 residents of PasiriDatariIndah Village who were included in the target. Cash Intensive Program. Based on the results of research that has been carried out regarding the Movement of Leaders in the Cash-Intensive Program in Pasir Datari Indah Village, CaringiniDistrict, Sukabumi Regency, using indicators of the mentoring process, giving instructions, and instructions, overall it has gone quite well. The mobilization process has been carried out quite well. The leadership movement in the Cash-Intensive Program in PasiriiDatar IndahiiVillage, Caringin..District, SukabumixRegency can be said to have been quite successful, but in practice it has not run optimally. But still, there needs to be optimization on socialization, as well as good communication with the community in order to improve the principles of self-help and participatory.